The membrane of peroxisomes in Saccharomyces cerevisiae is impermeable to NAD(H) and acetyl-CoA under in vivo conditions. - van Roermund, C W (1995)
We investigated how NADH generated during peroxisomal beta-oxidation is reoxidized to NAD+ and how the end product of beta-oxidation, acetyl-CoA, is transported from peroxisomes to mitochondria in Saccharomyces cerevisiae. Disruption of the peroxisomal malate dehydrogenase 3 gene (MDH3) resulted in impaired beta-oxidation capacity as measured in intact cells, whereas beta-oxidation was perfectly normal in cell lysates. In addition, mdh3-disrupted cells were unable to grow on oleate whereas growth on other non-fermentable carbon sources was normal, suggesting that MDH3 is involved in the reoxidation of NADH generated during fatty acid beta-oxidation rather than functioning as part of the glyoxylate cycle. To study the transport of acetyl units from peroxisomes, we disrupted the peroxisomal citrate synthase gene (CIT2). The lack of phenotype of the cit2 mutant indicated the presence of an alternative pathway for transport of acetyl units, formed by the carnitine acetyltransferase protein (YCAT). Disruption of both the CIT2 and YCAT gene blocked the beta-oxidation in intact cells, but not in lysates. Our data strongly suggest that the peroxisomal membrane is impermeable to NAD(H) and acetyl-CoA in vivo, and predict the existence of metabolite carriers in the peroxisomal membrane to shuttle metabolites from peroxisomes to cytoplasm and vice versa.